An Evaluation of Voluntary Varicella Vaccination Coverage in Zhejiang Province, East China - Hu, Yu (Int J Environ Res Public Health, 2016)
Background: In 2014 a 2-doses varicella vaccine (VarV) schedule was recommended by the Zhejiang Provincial Center for Disease Control and Prevention. We aimed to assess the coverage of the 1st dose of VarV (VarV(1)) and the 2nd dose of VarV (VarV(2)) among children aged 2–6 years through the Zhejiang Provincial Immunization Information System (ZJIIS) and to explore the determinants associated with the VarV coverage. Methods: Children aged 2–6 years (born from 1 January 2009 to 31 December 2013) registered in ZJIIS were enrolled. Anonymized individual records of target children were extracted from the ZJIIS database on 1 January 2016, including their VarV and (measles-containing vaccine) MCV vaccination information. The VarV(1) and VarV(2) coverage rates were evaluated for each birth cohorts. The coverage of VarV also was estimated among strata defined by cities, gender and immigration status. We also evaluated the difference in coverage between VarV and MCV. Results: A total of 3,028,222 children aged 2–6 years were enrolled. The coverage of VarV(1) ranged from 84.8% to 87.9% in the 2009–2013 birth cohorts, while the coverage of VarV(2) increased from 31.8% for the 2009 birth cohort to 48.7% for the 2011 birth cohort. Higher coverage rates for both VarV(1) and VarV(2) were observed among resident children in relevant birth cohorts. The coverage rates of VarV(1) and VarV(2) were lower than those for the 1st and 2nd dose of MCV, which were above 95%. The proportion of children who were vaccinated with VarV(1) at the recommended age increased from 34.6% for the 2009 birth cohort to 75.2% for the 2013 birth cohort, while the proportion of children who were vaccinated with VarV(2) at the recommended age increased from 19.7% for the 2009 birth cohort to 48.7% for the 2011 birth cohort. Conclusions: Our study showed a rapid increasing VarV(2) coverage of children, indicating a growing acceptance of the 2-doses VarV schedule among children’s caregivers and physicians after the new recommendation released. We highlighted the necessity for a 2-doses VarV vaccination school-entry requirement to achieve the high coverage of >90% and to eliminate disparities in coverage among sub-populations. We also recommended continuous monitoring of the VarV coverage via ZJIIS over time.